Dampak Tenaga Kerja, Tingkat Pendidikan, dan Kemiskinan terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Barat - Hilal; Mahmud , Ahmad Kafrawi; Umar, Mustofa (Bulletin of Economic Studies (BEST), 2022)
This study aims to determine whether labor, education level, and poverty affect economic growth in West Sulawesi Province. This research uses quantitative research. The data processing technique uses multiple linear regression through the SPSS 26 program. Secondary data is derived from historical records or reports arranged in published archives from 2006-2021. The results of this study indicate that the workforce has a positive and significant impact on economic growth in the Province of West Sulawesi. Furthermore, the level of education has a negative and significant effect on economic growth. Meanwhile, the poverty rate has no significant impact on economic growth.